Housing Price, Credit, and Output Cycles : How Domestic and External Shocks Impact Lithuania's Credit - Ioannou, Iacovos (IMF Working Papers; Working Paper, 2018)
Lithuania's current credit cycle highlights the strong link between housing prices and credit. We explore this relationship in more detail by analyzing the main features of credit, housing price, and output cycles in Baltic and Nordic countries during1995-2017. We find a high degree of synchronization between Lithuania's credit and housing price cycles. Panel regressions show a strong correlation between a credit upturn and housing price upturn. Moreover, panel VAR suggests that shocks in housing prices, credit, and output within and outside Lithuania strongly impact Lithuania's credit.